Commercial-off-the-shelf - Francis Hunger (Media Theory)
Using drone video material of the Ukraine war, this text updates Harun Farocki’s thesis of the operationalization of images to include the re-aestheticization of images. The article therefore looks into how originally operational images re-enter the sphere of representational images as war propaganda on social media. It contrasts drone war videos made with commercial-off-the-shelf drones with the imagery produced using the same drones by influencers. At the threshold between operationality and representation the text discusses how the drone video image stream becomes montage again, how a new, closer form of remoteness emerged with commercial-off-the-shelf drones, how the images are used as propaganda and “proof of work.” Finally, the distinction between infrastructural and public media (Schüttpelz, 2017) is discussed with the distinction of operational and representative images.